Factors related to mutilation and theft of library materials in PAASCU-Accredited (Level III) colleges and universities in Metro Manila - Rodis, Emerlita C. (Institute of Library Science, University of the Philippines Diliman, 1993)
This paper systematically dissects the library and academic factors, perceived by students, that possibly influence theft and mutilation of library books and materials. The 318 subjects of the study who were selected at random were enrolled in the accredited academic departments of eleven schools and universities in Metro Manila which are PAASCU - accredited (Level III). They were requested to answer the structured questionnaire prepared for the purpose. Interviews were also conducted with some willing respondents.